Cyber-physical design and optimization of tall building dynamics using aeroelastic wind tunnel modeling. Issue 198 (March 2020) - Fernández-Cabán, Pedro L.; Whiteman, Michael L.; Phillips, Brian M.; Masters, Forrest J.; Davis, Justin R.; Bridge, Jennifer A.
Abstract: This study explores the use of an automated cyber-physical system (CPS) framework for the design and optimization of tall building dynamics through aeroelastic boundary layer wind tunnel (BLWT) testing. The framework is fully automated, integrating experimental BLWT modeling with numerical optimization algorithms to rapidly evaluate a wide range of candidate designs. In this study, candidate tall building designs are generated by physically adjusting the dynamic properties of a multi-degree-of-freedom (MDOF) aeroelastic model. The specimen is equipped with an actuation system consisting of a series of variable stiffness devices (VSD), which enable precise control of the lower natural frequencies. The specimen is also instrumented with accelerometers and displacement sensors to capture wind-induced building response. A stochastic optimization algorithm evaluates the fitness of each candidate design based on code-based and/or user-specified serviceability limit states related to occupant comfort and building drift (e.g., sway). Wind tunnel experiments were conducted at the University of Florida Natural Hazard Engineering Research Infrastructure (NHERI) Experimental Facility. Results show that the CPS framework can reliably drive the aeroelastic specimen to the optimal solution which minimizes stiffness (i.e., natural frequency) while satisfying multiple acceleration and drift constraints. Highlights: Automated cyber-physical optimization of a building's dynamics in a wind tunnel. Aeroelastic model of a tall building at 1:200 scale. Variable stiffness devices to adjust the model's natural frequencies. Optimal designs meeting displacement and acceleration constraints. Explore-then-exploit metaheuristic optimization strategy.